The impact of Cohesion Policy 2007-2015 in EU regions: Simulations with the RHOMOLO Interregional Dynamic General Equilibrium Model - Francesco Di Comite; Patrizio Lecca; Philippe Monfort; Damiaan Persyn; Violeta Piculescu (European Commission, Joint Research Centre (JRC), 2018)
In this paper we assess the system-wide economic impact of the key financial instruments adopted by the European Union for the implementation of the regional policy: The Structural funds and The Cohesion Funds. We take a bottom-up approach by aggregating the 86 categories of expenditures defined in the Structural and Cohesion Funds into six main policy variables. The outcomes of the simulations are the results of a combination of demand-and-supply-side shocks that are implemented into the RHOMOLO spatial and dynamic general equilibrium model calibrated on a set of inter-regional Social Accounting Matrices for the year 2010. In our analysis we document the direct, indirect, and general equilibrium effects of the EU regional policy at the regional, national, and EU level. In the short-run, our simulation exercise suggests a pronounced variegate patters across EU regions. In the long-run, a more homogenous spatial distribution is detected. Moreover, we identify and quantify the interregional spillover effects arising from trade links and capital mobility.
Keywords: C54; C68; E62; R13; 330; rhomolo; region; growth; cohesion policy; modelling; general equilibrium